Upcycling of Waste Durian Peel into Valued Fe/N Co-Doped Porous Materials as Peroxymonosulfate Activator for Terramycin Oxidation - Kewang Zheng; Rui Liu; Lihang Shen; Wei Li; Caiqin Qin (Molecules)
Nitrogen-doped graphene-coated Fe nanoparticles (EC@N6Fe0.6-700) were synthesized through the pyrolysis of a durian peel-supported urea ferric salt mixture. These materials were subsequently utilized to activate peroxymonosulfate (PMS) for oxidation of terramycin (TEC). The incorporation of an optimal amount of urea and ferric nitrate during the synthesis of materials significantly improves the catalytic activity of the resulting catalysts after pyrolysis. Using EC@N6Fe0.6-700 catalyst at a concentration of 0.10 g L−1, 98.55% oxidation of 20 mg L−1 TEC is achieved within 60 min. Additionally, EC@N6Fe0.6-700 exhibits exceptionally low metal leaching, with levels remaining below 0.25 mg L−1. The EC@N6Fe0.6-700 shows remarkable stability during oxidation and effectively resists interference, reusability, and robust stability throughout the oxidation process. The mechanism of the EC@N6Fe0.6-700/PMS/TEC system is determined, and the 1O2 is the main reactive oxygen species (ROSs). The XPS analysis confirms that the primary active sites are Fe0, as well as nitrogen-doped regions within the carbon matrix. This research demonstrates that by integrating iron and nitrogen with durian peel, it is possible to develop a PMS activator with satisfactory oxidation performance for the degradation of environmental pollutants.